RANCANGAN PELAKSANAAN LAYANAN KONSELING INDIVIDUAL BERBASIS PENDEKATAN BEHAVIORAL DENGAN MENGGUNAKAN TEKNIK ASSERTIVE TRAINING BAGI PESERTA DIDIK KORBAN BULLYING {STUDI ANALISIS DESKRIPTIF DI SMA N 8 PADANG} - Cantika Meria Winnie; Fitria Kasih; Rahma Wira Nita (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This study is prompted by the issue of bullying, particularly the presence of students who are subjected to such behavior. The objective of this research is twofold: 1) To depict the characteristics of students who are victims of bullying, and 2) To devise a plan for implementing individual counseling services grounded in a behavioral approach utilizing Assertive Training techniques for students who are victims of bullying. The research methodology employed in this study is descriptive analysis. The study population consists of 3 students from SMA N 8 Padang who have experienced bullying. Sampling was conducted using the Total Sampling technique, wherein all members of the population were included as samples, totaling 3 individuals. Data was collected through a questionnaire and subsequently analyzed using percentage classification. The findings of the research indicate that: 1) The portrayal of students who are victims of bullying falls within the fairly high category, and 2) The framework for executing individual counseling services based on a behavioral approach utilizing Assertive Training techniques, focusing on addressing physical and verbal bullying, has been developed based on the identified issues and findings from bullying theory. Based on the outcomes of this study, it is suggested that BK teachers implement individual counseling services employing Assertive Training techniques for students at SMA N 8 Padang to address the challenges faced by students who are victims of bullying, as outlined in this research.